Relation between injury of the periaqueductal gray and central pain in patients with mild traumatic brain injury: Observational study. Issue 26 (June 2016) - Jang, Sung Ho; Park, So Min; Kwon, Hyeok Gyu
Abstract : Abstract: The periaqueductal gray (PAG) plays a pivotal role in pain modulation. We attempted to examine the relation between injury of the PAG and central pain in patients with mild traumatic brain injury (TBI). Sixty-one patients with mild TBI with central pain and 31 healthy control subjects were recruited for this study. Visual analog scale (VAS) was used for evaluation of central pain. The region of interest was defined for the PAG and the fractional anisotropy (FA) and apparent diffusion coefficient (ADC) were measured. The FA value was significantly lower in the patient group than in the control group ( P < 0.05). However, no significant difference in the ADC value was observed between the patient and control groups ( P > 0.05). VAS score of the patient group showed significant moderate negative correlation with the FA ( r = −0.38), while no significant correlation was observed between VAS score and the ADC value ( P < 0.05). We demonstrated injury of the PAG in patients with central pain following mild TBI and the degree of injury of the PAG was closely related to the degree of central pain.